Obstacles to Children's Growth and Development Due to Parental Cigarette Consumption in Sumatra - Purwaningsih, Vitriyani Tri; Putri, Resha Moniyana; Usman, Moneyzar; Pratama, Endriko Bagus (Universitas Muhammadiyah Yogyakarta, 2025)
Globally, one in three children under five are affected by stunting, which impairs their growth. On average, 50% of malnourished children aged five years or younger reside in Asia, while more than 30% live in Africa. Indonesia, as one of the Southeast Asian Countries, exhibits a higher prevalence of stunting compared to other middle-income countries. Several studies have identified a correlation between the smoking behavior of parents and the risk of stunting in children. This is thought to be due to the allocation of cigarette expenditure, which can reduce spending on food. This study aims to examine the impediments to growth encountered by children as a consequence of cigarette consumption within households in Sumatra and beyond. The data used in this study is derived from the Indonesian Family Life Survey (IFLS), with the logistic regression method utilized for analysis. The findings of this study indicate that a significant proportion of expenditure on cigarettes, living in a poor household, and internal child factors, namely the baby's weight at birth (less than 2500 grams), can increase the risk of children experiencing stunting. Genetic factors like parents' height and environmental factors like sanitation can also reduce the risk of stunting in children. Because the height of a parent’s body posture and a clean can positively influence children’s health conditions. The study calls for interventions to reduce smoking and improve child nutrition, especially in impoverished households. It is imperative to allocate expenditures related to the procurement of cigarettes to benefit children, thereby facilitating their growth and development.